2017
DOI: 10.1080/00223891.2017.1282493
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Aspects of the Depressive Experiences Questionnaire: Implications for Clinical Assessment and Research

Abstract: The Depressive Experiences Questionnaire (DEQ) is a self-report measure that assesses self-criticism and dependency, 2 personality traits that confer vulnerability to depression (Blatt, 2004 ). Over several decades, different, shortened versions of the DEQ have been constructed to offer an alternative to the complex scoring procedure of the original DEQ. This study explores the factor structure as well as the construct and convergent validity of the DEQ by comparing a clinical and nonclinical sample. We also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…This study explored the relationship between multidimensional anxiety, alexithymia, dependence and emotional-behavioral problems in adolescents. Consistent with previous studies, adolescents with anxiety symptoms have shown increased emotional-behavioral problems [45][46][47][48], and multidimensional anxiety. Negative personalities are positive predictors of adolescent emotional-behavioral problems [22].…”
Section: Discussionsupporting
confidence: 88%
“…This study explored the relationship between multidimensional anxiety, alexithymia, dependence and emotional-behavioral problems in adolescents. Consistent with previous studies, adolescents with anxiety symptoms have shown increased emotional-behavioral problems [45][46][47][48], and multidimensional anxiety. Negative personalities are positive predictors of adolescent emotional-behavioral problems [22].…”
Section: Discussionsupporting
confidence: 88%
“…This study explored the relationship between multidimensional anxiety, alexithymia, dependence and emotional-behavioral problems in adolescents. Consistent with previous studies, adolescents with anxiety symptoms have shown increased emotional-behavioral problems [45][46][47][48], and multidimensional anxiety.…”
Section: Discussionsupporting
confidence: 88%
“…This may indicate that being self-critical and dependent is associated with greater or more severe BPDs compared with being only highly self-critical. This is consistent with previous evidence that individuals presenting an elevated polarization with both relatedness and self-definition issues present more severe borderline psychopathological manifestations than individuals that develop only either dependent (i.e., focused on relatedness issues) or self-critical (i.e., focused on autonomy and self-definition concern) traits (Blatt, Quinlan, Chevron, McDonald, & Zuroff, 1982; Campos, Holden, Baleizão, Caçador, & Fragata, 2018; Falgares et al, 2018aa; Shahar, Blatt, & Ford, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Scores for both dependency and self-criticism were obtained using the original factor score procedure of Blatt, D'Afflitti, and Quinlan (1976). The Italian version of the DEQ showed good internal consistency and validity (see Falgares et al, 2017;Falgares et al, 2018a). In the present study, Cronbach's α was .81 in the nonclinical sample and .77 in the clinical sample (.81 pooling the samples together) for dependency, and .92 in the nonclinical sample and .90 in the clinical sample (.91 pooling the samples together) for self-criticism.…”
Section: Depressive Experiences Questionnairementioning
confidence: 99%